Preliminary Study on Energy Consumption at UiTMCPP library using IES simulation - Hussin, Norasikin; Baharum, Faizal; Abd Razak, Azli; Syihabuddin Suhaimi, Muhammad (International Journal of Engineering and Technology, 2018)
The Universiti Teknologi MARA Cawangan Pulau Pinang (UiTMCPP) library building was consists of three-story including office, reading area, multi-media room, and meeting room. Based on the library record where the average number of students coming to the library is 257 students per day. In other words for an hour, only 17 students have come to the library. The occupantâ€™s claimed that they feel uncomfortable because of the cold temperature in the building. Currently, the air conditionerâ€™s setting temperature of the building is 17ÂºC and does not follow the requirement in the Malaysia Standard, MS1525. Therefore, the aim of this case study is to investigate the thermostat temperature in order to control the energy consumption and cost of saving in the library building. In this work, the set point was changed from 17ÂºC to 20ÂºC. This adjustment was referring to the MS1525. The IES<VE> software is used as the energy simulation tool to calculate and compare electricity cost and energy consumption. The finding from the simulation shows the annual energy consumption at 17Â°C and 20Â°C are 6.14Gwh per year and 5.03Gwh per year, respectively.Â Thus, the energy saving was increased by 1.11Gwh per year and cost of electricity was save by RM402 thousands per annum.Â Finally, it can be shown that the raising of the set point can minimize the energy consumption and electricity cost with 18% reduction per year.Â Â